Hepatocyte‐Specific β‐Catenin Deletion During Severe Liver Injury Provokes Cholangiocytes to Differentiate Into Hepatocytes. Issue 2 (4th January 2019) - Russell, Jacquelyn O.; Lu, Wei‐Yu; Okabe, Hirohisa; Abrams, Marc; Oertel, Michael; Poddar, Minakshi; Singh, Sucha; Forbes, Stuart J.; Monga, Satdarshan P.
Abstract : Liver regeneration after injury is normally mediated by proliferation of hepatocytes, although recent studies have suggested biliary epithelial cells (BECs) can differentiate into hepatocytes during severe liver injury when hepatocyte proliferation is impaired. We investigated the effect of hepatocyte‐specific β‐catenin deletion in recovery from severe liver injury and BEC‐to‐hepatocyte differentiation. To induce liver injury, we administered choline‐deficient, ethionine‐supplemented (CDE) diet to three different mouse models, the first being mice with deletion of β‐catenin in both BECs and hepatocytes ( Albumin‐Cre; Ctnnb1 flox/flox mice). In our second model, we performed hepatocyte lineage tracing by injecting Ctnnb1 flox/flox ; Rosa‐stop flox/flox ‐EYFP mice with the adeno‐associated virus serotype 8 encoding Cre recombinase under the control of the thyroid binding globulin promoter, a virus that infects only hepatocytes. Finally, we performed BEC lineage tracing via Krt19‐Cre ERT ; Rosa‐stop flox/flox ‐tdTomato mice. To observe BEC‐to‐hepatocyte differentiation, mice were allowed to recover on normal diet following CDE diet–induced liver injury. Livers were collected from all mice and analyzed by quantitative real‐time polymerase chain reaction, western blotting, immunohistochemistry, and immunofluorescence. We show that mice with lack of β‐catenin in hepatocytes placed on the CDE diet develop severe liver injury with impaired hepatocyte proliferation, creating a stimulus for BECs to differentiate into hepatocytes. In particular, we use both hepatocyte and BEC lineage tracing to show that BECs differentiate into hepatocytes, which go on to repopulate the liver during long‐term recovery. Conclusion : β‐catenin is important for liver regeneration after CDE diet–induced liver injury, and BEC‐derived hepatocytes can permanently incorporate into the liver parenchyma to mediate liver regeneration.